PENERAPAN COOPERATIVE PROFESSIONAL DEVELOPMENT MODEL DALAM SUPERVISI AKADEMIK UNTUK MENINGKATKAN INOVASI DALAM PEMBELAJARAN GURU DI SMP NEGERI 1 DONOROJO (Harmony: Jurnal Pembelajaran IPS dan PKN, 2019)
The purpose of this research to know how to use the cooperative professional development model of Academic supervision to improve teacher innovation in learning at Donorojo 1 Junior High School in 2017/2018 academic year and knowing that the implementation of the cooperative professional development model in academic supervision can improve teacher innovation in learning in Donorojo 1 Junior High School 2017/2018 academic year. Application of cooperative professional development model in academic supervision to improve innovation in teacher learning in Donorojo 1 Junior High School 2017/2018 academic year is packaged in the form of action research, namely the School Action Research (PTS) which is carried out through a continuous cycle. The results of the School Action Research can be concluded that the application of cooperative professional development models in academic supervision can improve innovation in teacher learning, as evidenced by: (i) Teacher motivation in collecting learning planning administration, namely from the pre-cycle of 19 teachers (67.87 %) to 28 teachers (100%) in the first cycle and second cycle, so that it can increase 32.13%; (ii) Final planning administration value in cycle I was 79.69% to 83.85% in cycle II, so that it could increase by 4.16%; (iii) Observation of planning administration in the first cycle of 88.80% to 94.48% in the second cycle, so that it can increase by 5.68%; (iv) The final grade in the classroom increased from 79.81% in the first cycle to 83.54% in the second cycle, resulting in an increase of 3.73%; and (v) The final value of the assessment of student learning outcomes increased, from the first cycle 79.40% to 85.10% in the second cycle, so there was an increase of 5.70%. Penelitian ini bertujuan untuk mengetahui cara menerapkan cooperative professional development model dalam supervisi akademik untuk meningkatkan inovasi guru dalam pembelajaran di SMP Negeri 1 Donorojo Tahun pelajaran 2017/2018 dan mengetahui bahwa penerapan cooperative professional development model dalam supervisi akademik dapat meningkatkan inovasi guru dalam pembelajaran di SMP Negeri 1 donorojo Tahun pelajaran 2017/2018.Penerapan cooperative professional development model dalam supervisi akademik untuk meningkatkan inovasi dalam pembelajaran guru di SMP Negeri 1 Donorojo Tahun pelajaran 2017/2018 dikemas dalam bentuk penelitian tindakan (action research). Hasil Penelitian Tindakan Sekolah (PTS) ini dapat disimpulkan bahwa penerapan cooperative professional development model dalam supervisi akademik dapat meningkatkan inovasi dalam pembelajaran guru, dibuktikan dengan: (i) Motivasi guru dalam mengumpulkan administrasi perencanaan pembelajaran, yaitu dari prasiklus adalah 19 guru (67,87%) menjadi 28 guru (100%) pada siklus I dan siklus II, sehingga dapat meningkat 32,13%; (ii) Nilai akhir administrasi perencanaan pada siklus I sebesar 79,69% menjadi 83,85% pada siklus II, sehingga dapat meningkat sebesar 4,16%; (iii) Pengamatan administrasi perencanaan pada siklus I sebesar 88,80% menjadi 94,48% pada siklus II, sehingga dapat meningkat sebesar 5,68%; (iv) Nilai akhir pelaksanaan dikelas meningkat dari 79,81% pada siklus I menjadi 83,54% pada siklus II, sehingga terjadi peningkatan sebesar 3,73%; dan (v) Nilai akhir penilaian hasil pembelajaran siswa meningkat, dari siklus I 79,40% menjadi 85,10% pada siklus II, sehingga ada peningkatan 5,70%.